PERTANGGUNGJAWABAN ALOKASI DANA DESA PELAGA TERKAIT PROGRAM PEMBERIAN ALOKASI DANA DESA KABUPATEN BADUNG - Sugiantari, Anak Agung Putu Wiwik; Wiasta, I Wayan; Perbawa, Ketut Sukawati Lanang Putra; Wiryawan, I Wayan Gde; Wijaya, I Made Hendra (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
With the enactment of Act Number 6 of 2014 concerning the Village, then granting of Village Fund by Local Government of Badung to Pelaga Village, requires a of acccountability for the use of aid allocations Village Fund. In this research discusses the Badung regency government policy in managing the allocation of village funds and the accountability Village Revenues and Expenditures Budget in Pelaga Village, Petang District, Badung Regency.